(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to evaluate on the effects of mother’s thyroid autoantibodies on intrauterin fetal death.Meterial and Methods: A total of 200 pregnant women aged between 18 and 40 in their 6th-12th weeks of pregnancy were included in this study. The first group (study group) included 100 pregnant women who had previously experienced pregnancy loss in the second trimester in their previous pregnancies (termination of the pregnancy in the 13th-28th gestational weeks due to intrauterine fetal death). The second group (control group) also had 100 patients.Results: There is no statistically significant difference between the two groups in terms of age, number of pregnancies, and miscarriages (p>0.05). The avarage serum level of anti-thyroid peroxidase in the study group was higher than the control group (p=0.009). But when anti-thyroglobulin and anticardiolipin IgG levels were evaluated, we have seen that there was no difference between the two groups (p>0.05). Moreover, the ratio of pregnant women who had positive anti-thyroid peroxidase was %3 in the control group and %11 in the study group. This was considered statistically high (p=0.027). The correlation between the presence of thyroid autoantibodies and antiphospholipid antibody positivity was statistically low.Conclusion: Thyroid autoantibodies can be one of the autoimmune factors that are responsible for pregnancy loss. They show their effects by making a direct impact on the fetoplasental unit, causing thyroid malfunction, or creating an imbalance in the immune system of the mother. However, the role of thyroid autoantibodies on pregnancy losses are not clear and controlled studies are needed.